Ultrasound Imaging and Antithrombotic Effects of PLA-Combined Fe3O4-GO-ASA Multifunctional Nanobubbles - Zhang, Jie; Liu, Zheng; Chang, Cunyi; Hu, Ming; Teng, Yang; Li, Jinjing; Zhang, Xiangyu; Chi, Yanxia (Frontiers in Medicine, 2021)
PLA combined ferroferric oxide - graphene oxide - aspirin (Fe3O4-GO-ASA) multifunctional nanobubbles were prepared by the double emulsion-solvent evaporation method. The obtained composite nanobubbles had a regular spherical shape, Zeta potential of (-36.5±10.0) mV, particle size distribution range of 200-700nm. The experimental results showed that PLA combined Fe3O4-GO-ASA nanobubbles could effectually improve the antithrombin parameters of PT, TT, APTT and INR, and significantly inhibit thrombosis when the composite nanobubbles with a concentration of 80 mg·mL-1 interacted with the rabbit blood. The prepared composite nanobubbles could reach a significant ultrasonic imaging effect and good magnetic targeting under the magnetic field when the nanobubbles concentration was only 60 mg·mL-1.